Maternal-fetal toxicity of Strychnos pseudoquina extract treatment during pregnancy - Souza, Maysa Rocha [UNESP]; Brito, Evelyn Caroline Barbosa; Furtado, Linne Stephane; Barco, Vinícius Soares [UNESP]; Cruz, Larissa Lopes da [UNESP]; Moraes-Souza, Rafaianne Queiroz [UNESP]; Monteiro, Gean Charles [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; Damasceno, Débora Cristina [UNESP]; Volpato, Gustavo Tadeu (Elsevier, 2023)
Ethnopharmacological relevance: Plants and herbs have been used by women throughout history for therapeutic purposes. Strychnos pseudoquina, a plant used in the treatment of various diseases, can also function as an abortive herb. There is no scientific confirmation of its effects during pregnancy, and the activity of this plant needs to be substantiated or refuted with experimental evidence. Aim of the study: Evaluating the effect of the S. pseudoquina aqueous extract on maternal reproductive toxicity and fetal development. Materials and methods: The aqueous extract of S. pseudoquina bark was evaluated in Wistar rats. Pregnant rats were distributed into four experimental groups (n = 12 rats/group): Control = treated with water (vehicle); Treated 75, Treated 150, and Treated 300 = treated with S. pseudoquina at dose 75, 150 and 300 mg/kg, respectively. The rats were treated by an intragastric route (gavage) from day 0 to day 21 of pregnancy. At the end of pregnancy, maternal reproductive outcomes, organs, biochemical and hematological profiles, fetuses, and placentas were analyzed. Maternal toxicity was evaluated through body weight gain, water, and food intake. With knowledge of the harmful dosage of the plant, other rats were used on gestational day 4 for the evaluation of morphological analyses before embryo implantation. P < 0.05 was considered as statistically significant. Results: The S. pseudoquina treatment showed elevated liver enzymatic activities. The Treated 300 group presented toxicity with reduced maternal body weight, water and food intake, and increased kidney relative weight compared to those of the Control group. At a high dosage, the plant presents an abortifacient activity, confirmed by embryo losses before and after implantation and degenerated blastocysts. In addition, the treatment contributed to an increased percentage of fetal visceral anomalies, decreased ossification sites, and intrauterine growth restriction (300 mg/kg dose). Conclusion: In general, our study showed that an aqueous extract of S. pseudoquina bark caused significant abortifacient activity that testified to its traditional use. Furthermore, the S. pseudoquina extract caused maternal toxicity that contributed to impaired embryofetal development. Therefore, the use of this plant should be completely avoided during pregnancy to prevent unintended abortion and risks to maternal-fetal health.
Keywords: Abortion; Malformations; Medicinal plants; Rats; S. pseudoquina; Uterus